Modelling random antibody adsorption and immunoassay activity - D. Mackey; E. Kelly; R. Nooney (Mathematical Biosciences and Engineering)
One of the primary considerations in immunoassay design is optimizingthe concentrationof capture antibodyin order to achieve maximal antigen binding and, subsequently, improved sensitivityand limit of detection.Many immunoassay technologies involve immobilizationof theantibody to solid surfaces.Antibodies are large molecules in whichthe position and accessibility of the antigen-binding sitedepend on their orientation and packing density. In this paper we propose a simple mathematical model, based on the theoryknown as random sequential adsorption (RSA), in order tocalculate how the concentration ofcorrectly oriented antibodies (active site exposed forsubsequent reactions) evolves during the deposition process.It has been suggested by experimental studies that high concentrationswill decrease assay performance, due to molecule denaturation andobstruction of active binding sites. However, crowding of antibodies can alsohave the opposite effect by favouring upright orientations.A specific aim of our model is topredict which of thesecompeting effects prevails under different experimental conditionsand study the existence of an optimalcoverage, which yields the maximum expectedconcentration of activeparticles (and hence the highest signal).